Pursuing parity: genetic tests for psychiatric conditions in the UK National Health Service. (22nd March 2019) - Curtis, David; Adlington, Katherine; Bhui, Kamaldeep S.
Summary: Schizophrenia and anorexia nervosa were recently added to the list of conditions for which whole genome sequencing might be indicated as part of the 100 000 Genomes Project, reflecting the remarkable recent progress in findings emerging from psychiatric genetics research. Genetic testing methods may offer increased opportunities for diagnosis and estimation of familial risk and could have implications for management and treatment options. They also present ethical and philosophical questions about the role of testing and storage of genetic information. Mental health professionals will need to have a good understanding of this area in order for patients to fully realise the benefits of these advances. Declaration of Interest: K.S.B. is Editor of the British Journal of Psychiatry .